An association between an organic foreign body and persisting itching-A case report - Yulia Treister-Goltzman; Yan Press; Roni Peleg (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2019)
Background: To our knowledge there has been no previous report in the literature of persistent diffuse itching caused by an organic foreign body. Case presentation: The patient, 81-year-old woman, had suffered over the previous six months from diffuse itching of the scalp, the chest, and the abdomen. Her multiple chronic diseases and extensive laboratory tests didn't explain the itching. The itching was accompanied by the appearance of red blotches on the skin. When a repeat history was taken the patient related that she had fallen in an open field six months earlier and felt a stabbing sensation in her lower abdomen. A repeat examination revealed a small lesion on the skin about 4cm below the umbilicus. Beneath the skin lesion a fluid collection that was sensitive to touch could be palpated. The collection was drained and the splinter removed, the patient reported significant improvement in the itching, which almost completely disappeared without a need for medication. Conclusion: The itching began soon after the patient fell and the splinter penetrated the abdominal wall tissue and only stopped after the splinter was removed. This leads us to assume that the organic foreign body was the cause of the persistent itching. As in many other cases a good history and careful physical examination can lead to the solution of a perplexing medical diagnostic problem.